(untitled) (Journal of the College of Basic Education, 2022)
TV advertising is a promotional process for a specific commodity or a specific commodity or a specific message for a specific goal. Advertising is of great importance in marketing and the success of projects that include consumer goods as well. Aesthetic, dramatic and intellectual seeking to attract and attract the attention of the recipient towards the advertisement and thus the delivery of the advertisement message to him and from this it is clear the importance of this research, through a solution to the following question represented by the research problem: - How is TV advertising constructed technically? The theoretical framework in the research also included two topics, the first topic (the concept of modern television advertising), and the second topic is (the work of cinematic language elements in the television advertising) and the two researchers came out with a set of indicators from the theoretical framework and the most important 1- Employing the elements of the display language inside the advertisement that enhances its role in marketing the ideas and products of companies. 2- Including positive ideas in the structure of advertising as an indirect marketing method for companies ’products. The most important results that resulted from this research after analyzing a group of samples... 1- Elements of technical language had a great role in enhancing the ability of the advertisement to communicate its message effectively and effectively. 2- Including positive thoughts that call for charity, good deeds, morals, and higher social values ​​that contribute effectively to the delivery of the advertising message 3- Exploiting socially influencing issues that contribute significantly to creating a state of empathy by the public towards advertising